G2/M Checkpoint Abrogation With Selective Inhibitors Results in Increased Chromatid Breaks and Radiosensitization of 82-6 hTERT and RPE Human Cells - Nikolakopoulou, Aggeliki; Soni, Aashish; Habibi, Martha; Karaiskos, Pantelis; Pantelias, Gabriel; Terzoudi, Georgia I.; Iliakis, George (Frontiers in Public Health, 2021)
While technological advances in radiation oncology have led to a more precise delivery of radiation dose and a decreased risk of side effects, there is still a need to better understand the mechanisms underlying DNA damage response (DDR) at the DNA and cytogenetic levels, and to overcome tumor resistance. To maintain genomic stability, cells have developed sophisticated signaling pathways enabling cell cycle arrest to facilitate DNA repair via the DDR-related kinases and their downstream targets, so that DNA damage or DNA replication stress induced by genotoxic therapies can be resolved. ATM, ATR, and Chk1 kinases are key mediators in DDR activation and crucial factors in treatment resistance. It is of importance, therefore, as an alternative to the conventional clonogenic assay, to establish a cytogenetic assay enabling reliable and time-efficient results in evaluating the potency of DDR inhibitors for radiosensitization. Toward this goal, the present study aims at the development and optimization of a chromosomal radiosensitivity assay using the DDR and G2-checkpoint inhibitors as a novel modification compared to the classical G2-assay. Also, it aims at investigating the strengths of this assay for rapid radiosensitivity assessments in cultured cells, and potentially, in tumor cells obtained from biopsies. Specifically, exponentially growing RPE and 82-6 hTERT human cells are irradiated during the G2/M-phase transition in the presence or absence of Caffeine, VE-821, and UCN-1 inhibitors of ATM/ATR, ATR, and Chk1, respectively, and the induced chromatid breaks are used to evaluate cell radiosensitivity and their potency for radiosensitization. The increased yield of chromatid breaks in the presence of DDR inhibitors, which underpins radiosensitization, is similar to that observed in cells from highly radiosensitive AT-patients, and is considered here as 100% radiosensitive internal control. The results highlight the potential of our modified G2-assay using VE-821 to evaluate cell radiosensitivity, the efficacy of DDR inhibitors in radiosensitization, and reinforce the concept that ATM, ATR, and Chk1 represent attractive anticancer drug targets in radiation oncology.